Amino acid substitutions involved in the adaptation of a novel highly pathogenic H5N2 avian influenza virus in mice. Issue 1 (December 2016) - Wu, Haibo; Peng, Xiuming; Peng, Xiaorong; Wu, Nanping
Abstract Background H5N2 avian influenza viruses (AIVs) can infect individuals that are in frequent contact with infected birds. In 2013, we isolated a novel reassortant highly pathogenic H5N2 AIV strain [A/duck/Zhejiang/6DK19/2013(H5N2) (6DK19)] from a duck in Eastern China. This study was undertaken to understand the adaptive processes that led enhanced replication and increased virulence of 6DK19 in mammals. 6DK19 was adapted to mice using serial lung-to-lung passages (10 passages total). The virulence of the wild-type virus (WT-6DK19) and mouse-adapted virus (MA-6DK19) was determined in mice. The whole-genome sequences of MA-6DK19 and WT-6DK19 were compared to determine amino acid differences. Findings Amino acid changes were identified in the MA-DK19 PB2 (E627K), PB1 (I181T), HA (A150S), NS1 (seven amino acid extension "WRNKVAD" at the C-terminal), and NS2 (E69G) proteins. Survival and histology analyses demonstrated that MA-6DK19 was more virulent in mice than WT-6DK19. Conclusion Our results suggest that these substitutions are involved in the enhanced replication efficiency and virulence of H5N2 AIVs in mammals. Continuing surveillance for H5N2 viruses in poultry that are carrying these mutations is required.